Editorial Comment on: D. Schreiber-Dietrich, M. Pohl, X.W. Cui, B. Braden, C.F. Dietrich, L. Chiorean Perihepatic lymphadenopathy in children with chronic viral hepatitis - Katarzyna Gruszczyńska; Jan Baron (Journal of Ultrasonography, 2015)
The article entitled Perihepatic lymphadenopathy in children with chronic viral hepatitis(1) is an original paper of high clinical relevance – viral hepatitis B and C are the main causes of chronic hepatitis and liver cirrhosis in children. Based on ultrasound fi ndings, the authors assessed the presence of the perihepatic lymph nodes and their morphology in 49 children with chronic viral hepatitis B and C (38 and 11 children, respectively). The authors hoped that this investigation would help establish a new, non-invasive marker enabling screening examinations to be conducted in children with chronic viral hepatitis. In adults, a correlation was found between the activity of hepatitis and the morphology of the lymph nodes in a US examination, but such a correlation has, until now, not been reported in children(2–4). The results of the study have a clinically signifi cant aspect – the loops of the hepatoduodenal ligament are relatively readily available in a transabdominal examination, and ultrasonography is an inexpensive and safe method to be conducted in children.